TLR-Dependent Human Mucosal Epithelial Cell Responses to Microbial Pathogens - McClure, Ryan; Massari, Paola (Frontiers in Immunology, 2014)
Abstract Toll-Like Receptor (TLR) signaling represents one of the best studied pathways to implement defense mechanisms against invading microbes in humans as well as in animals. TLRs respond to specific microbial ligands and to danger signals produced by the host during infection, and initiate downstream cascades that activate both innate and adaptive immunity. TLRs are expressed by professional immune cells and by the large majority of non-hematopoietic cells, including epithelial cells. In epithelial tissues, TLR functions are particularly important because these sites are constantly exposed to microorganisms, due to their location at the host interface with the environment. While at these sites, specific defense mechanisms and inflammatory responses are initiated via TLR signaling against pathogens, suppression or lack of TLR activation is also observed in response to the commensal microbiota. The mechanisms by which TLR signaling is regulated in mucosal epithelial cells include differential expression and levels of TLRs (and their signaling partners), their cellular localization and positioning within the tissue in a fashion that favors responses to pathogens while dampening responses to commensals and maintaining tissue homeostasis in physiologic conditions. In this review, the expression and activation of TLRs in mucosal epithelial cells of several sites of the human body are examined. Specifically, the oral cavity, the ear canal and eye, the airways, the gut and the reproductive tract are discussed, along with how site-specific host defense mechanisms are implemented via TLR signaling.